Efficacy of the Mirasol pathogen reduction technology system against severe fever with thrombocytopenia syndrome virus (SFTSV). Issue 4 (1st June 2015) - Shinohara, N.; Matsumoto, C.; Chatani, M.; Uchida, S.; Yoshikawa, T.; Shimojima, M.; Satake, M.; Tadokoro, K.
<x xml:space="preserve">Abstract</x> Severe fever with thrombocytopenia syndrome virus (SFTSV) is a tickborne virus in the Bunyaviridae family. This virus has recently been found in China, Japan and Korea. The risk of transfusion‐transmitted SFTSV infection (TTI‐SFTSV) is a concern because person‐to‐person transmission resulting from contact with SFTSV‐contaminated blood has been reported. Therefore, we investigated the efficacy of the Mirasol pathogen reduction technology (PRT) system for inactivating SFTSV in vitro. The Mirasol PRT system achieved a > 4·11 log10 reduction value (LRV) for SFTSV. In conclusion, we showed that the Mirasol PRT system could potentially be used to reduce the risk of TTI‐SFTSV.